Btr02, a TRIM39 gene is related to the hypoxia tolerance of Megalobrama amblycephala - Shan-Shan Zhao; Guo-Dong Zheng; Shu-Ming Zou (Aquaculture Reports)
Megalobrama amblycephala is susceptible to hypoxia, which results high mortality rates in aquaculture. A preliminary study on a new variety of M. amblycephala called ''Pujiang No.2'' (GS-01–002–2020) discovered that its tolerance to hypoxia was significantly improved compared with that of wild breed. The objective of this study was to identify the key genes responsible for the enhanced hypoxia tolerance of this new variety. Based on previous RNA sequencing results, the function of btr02 (bloodthirsty-like tripartite motif [TRIM] 02 gene), a key gene for hypoxia tolerance, was explored using CRISPR/Cas9. The results demonstrated that the mutation rate of M. amblycephala btr02+/- was 39.38 %. The 5-month-old mutant was of the same size as normal individuals; however, its tolerance to hypoxia decreased substantially. Specifically, the LOEcrit of knockout mutants increased significantly (P<0.01), and the activity of antioxidant enzymes and the number of erythrocytes decreased significantly (P<0.01) after hypoxia stress. Nevertheless, there was no significant difference in gill morphology between mutant and control groups after hypoxia. These results imply that the btr02 gene of M. amblycephala influences the ability of fish to adapt to hypoxia by affecting the antioxidant stress processes and erythrocyte production.